Teachers’ Self-Efficacy and the Use of Assistive Technologies in Inclusive Public Secondary Schools in Tanzania - Ambrose Sichela; Gabriel Walubita (Indonesian Educational Research Journal, 2026)
Inclusive education is one of the policy agendas that are given priority in most nations, including Tanzania. The effective use of assistive technologies is among the important aspects of inclusion practice in a classroom, providing students with diverse needs with an opportunity to access the curriculum content and learn. There is however evidence to suggest that use of assistive technologies in inclusive secondary schools is still minimal, especially in low-resource settings. This paper was based on the Social Cognitive Theory and the Technology Acceptance Model, in examining the relationship between teacher self-efficacy and the use of assistive technologies in inclusive public secondary schools in Tanzania. Quantitative research approach with correlational research design was employed. Validated questionnaires were used to collect data that measured the self-efficacy and the use of assistive technology among 180 teachers selected from 15 inclusive public secondary schools in four regions. Descriptive statistics demonstrated a moderate level of teacher self-efficacy and moderate level use of assistive technology, yet differences existed among the domains of self-efficacy. Furthermore, the findings showed that there was a statistically significant positive correlation between self-efficacy of teachers and the use of assistive technology (r=.50, p˂.001). The results indicated that there is a need to increase teachers’ confidence and support systems in regard to improving the effective implementation of inclusive education practices